Sekundärmalignome in Harnableitungen - Kälble, Tilman; Alken, Peter (Der Urologe, 2012)
In contrast to ureterosigmoidostomy no reliable clinical data exist for tumor risk in different forms of urinary diversion using isolated intestinal segments.In 44 German urological departments, operation frequencies, indications, patient age, and operation dates of the different forms of urinary diversion, operated between 1970 and 2007, could be registered. The secondary tumors up to 2009 were registered as well and related to the numbers of the different forms of urinary diversions resulting in tumor prevalences.In 17,758 urinary diversions 32 secondary tumors occurred. The tumor risk in ureterosigmoidostomy (22-fold) and cystoplasty (13-fold) is significantly higher than in other continent forms of urinary diversion such as neobladders or pouches (p<0.0001). The difference between ureterosigmoidostomy and cystoplasty is not significant, nor is the difference between ileocecal pouches (0.14%) and ileal neobladders (0.05%) (p=0.46). The tumor risk in ileocecal (1.26%) and colonic neobladders (1.43%) is significantly higher (p=0.0001) than in ileal neobladders (0.5%). Of the 16 tumors that occurred following ureterosigmoidostomy, 16 (94%) developed directly at the ureterocolonic borderline in contrast to only 50% following urinary diversions via isolated intestinal segments.From postoperative year 5 regular endoscopic controls of ureterosigmoidostomies, cystoplasties, and orthotopic (ileo-)colonic neobladders are necessary. In ileocecal pouches, regular endoscopy is necessary at least in the presence of symptoms or should be performed routinely at greater intervals. Following neobladders or conduits, only urethroscopies for urethral recurrence are necessary.